THE EFFECT OF SUPRASEGMENTAL PRONUNCIATION ON SPEAKING SKILLS OF BUGINESE EFL LEARNERS - Mayadah, Mayadah; DJ., Muhammad Zuhri; Nur, Hasriati (Institut Agama Islam Negeri (IAIN) Bone, 2024)
AbstractThe objective of this research was to describe how the effect of Suprasegmental Pronunciation affects the Speaking Skills of Buginese EFL Learners. Qualitative method was used in this research with the implementation of descriptive qualitative method. Furthermore, the research instruments such as observation and interview were used to collect data in this research. This research was conducted at Institut Agama Islam Negeri (IAIN) Bone with the implementation done in the classroom for Speaking classes. There were 4 students as participants in this research who were selected by purposive sampling. Based on the results of the reserach, it was found that Suprasegmental Pronunciation has positive impacts that show how the Suprasegmental pronunciation affects their speaking skills in a good way such as ease of understanding the meaning of the words, conversation becomes more natural, conveying emotions, and a plus point in terms of communication skills. Moreover, it also found that there are negative effects on Speaking Skills of Buginese EFL learners such as speaking anxiety and local suprasegmental pronunciation is hardly separated.